2000
DOI: 10.1053/jhep.2000.8270
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C–related cirrhosis: A predictor of diabetes after liver transplantation

Abstract: Hepatitis C virus (HCV) infection has recently been suggested to be a risk factor for the development of diabetes mellitus. The aim of our study was to investigate whether the prevalence of diabetes is increased among liver transplant recipients infected with HCV. We compared the prevalence of diabetes among 278 liver transplant recipients whose original cause of liver failure was HCV infection (110 patients), hepatitis B virus infection (HBV; 53 patients), and cholestatic liver disease (CLD; 115 patients). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
104
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 26 publications
8
104
2
3
Order By: Relevance
“…In this report, we found a prevalence of DM greater than 50% in liver transplant candidates with liver cirrhosis in contrast to its lower incidence in other series. [12][13][14][15][16][17] A factor that may contribute to this difference is the low proportion of patients with cholestatic liver disease in our series compared with others. Zein et al 16 found a lower prevalence of DM in patients with chronic cholestasis than in those with liver cirrhosis caused by hepa- titis C or alcohol.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this report, we found a prevalence of DM greater than 50% in liver transplant candidates with liver cirrhosis in contrast to its lower incidence in other series. [12][13][14][15][16][17] A factor that may contribute to this difference is the low proportion of patients with cholestatic liver disease in our series compared with others. Zein et al 16 found a lower prevalence of DM in patients with chronic cholestasis than in those with liver cirrhosis caused by hepa- titis C or alcohol.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, other studies did not show a difference between patients with and without DM. 12,[14][15][16][17] In these studies, DM had been diagnosed according to serum fasting glucose levels, probably underestimating the incidence of liver cirrhosis-related DM.The aim of this study is to investigate the prevalence of pre-OLT DM in end-stage liver cirrhosis and assess the evolution of patients with DM after OLT. In addition, factors predisposing to post-OLT DM were studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of universal agreement, some studies have observed worsened short-and mid-term survival among diabetic LT recipients. [1][2][3][4][5][6][7] Furthermore, DM is a wellknown risk factor for cardiovascular disease, which is one of the leading causes of death of LT recipients in the long term. 8 Calcineurin inhibitors (CI) also predispose to DM through islet cell toxicity, diminished insulin synthesis or release, as well as decreased peripheral insulin sensitivity.…”
Section: D Abetes Mellitus (Dm)mentioning
confidence: 99%
“…5 Moreover, new-onset type 2 DM is common among patients undergoing liver transplantation and occurs in 37% of patients undergoing transplantation for HCV versus a prevalence of 10% or less for those undergoing transplantation for other indications. 6 One of our own studies by Foxton et al 7 demonstrated that developing DM either before or after transplantation played a significant role in the progression of graft fibrosis in HCV patients. In our cohort, among the 163 patients who fulfilled the criteria to be included in the study, 54 patients called ''fast and rapid progressors'' had progressed to stage 4 fibrosis or higher at the time of censoring.…”
mentioning
confidence: 98%